Pragmatics and the English language - Culpeper, Jonathan (Palgrave Macmillan, 2014)
While covering typical pragmatics topics, this book presents a new view on pragmatics: integrative pragmatics. It is comprehensive in its coverage, yet incorporates state-of-the-art research. Examples and case studies throughout connect theory with data, and illuminate how pragmatics phenomena and concepts are realised or tempered in English